Pengaruh Gaya Hidup Konsumtif dan Kualitas Produk Terhadap Keputusan Pembelian - Aini, Eni Nur; Andjarwati, Anik Lestari (BISNIS, 2020)
Along with the development of the hijab model in Indonesia which is a market need and can develop the creativity of fashionable hijab. From year to year Zoya continues to provide new creations and innovations to her hijab designs. Ranging from exclusive designs to promotional materials that continue to give priority to the comfort of its users. Various awards ranging from Top Brand to Best Band achieved in three years were agreed. Based on this phenomenon, this study discusses the consumptive lifestyle and product quality on Zoya hijab purchasing decisions in Central Surabaya. This research method uses quantitative methods by studying causal with multiple linear regression techniques using the IBM SPSS 23 for windows program. Consumptive lifestyle and product quality as independent variables and purchasing decisions as the dependent variable. The object of this research is the Zoya brand quadrilateral consumers with a sample of 220 respondents. The results showed that the consumptive lifestyle influenced purchasing decisions by 0.225, but the results differed on the product quality variable by 0.080 that did not affect the purchasing decision.